A STUDY ON ENGLISH LITERATURE STUDENTS’ ANXIETY IN LEARNING ENGLISH - Muhammad Taufik (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The research is aims to describe types and causes of speking anxiety English literature faculty students, Makassar Islamic university. Towards students from semester 5 and 3, there are six students of English literature who are the subject of study. This study used descriptive qualitative method by using online studies by calling and watching a video. Data were taken from the speaking students in a learning video. Research result show there are 39 types of anxiety and 20 causes anxiety which is found from the expression and the way students speak in English, namely 6 types of reality or objective anxiety, 7 types of neurotic anxiety, and 6 types of moral anxiety.